Mathematical Reasoning Ability Based on Self Regulated Learning by Using The Learning of Reciprocal Teaching With RME Approach - Astuty, Eny Sri Wiji; Waluya, St Budi; Sugianto, Sugianto (Unnes Journal of Mathematics Education Research, 2019)
The purpose of this study was (1) determine the quality of mathematics learning in the class taught with the RME-approached Reciprocal Teaching learning model, and (2) to find out the description of the mathematical reasoning ability based on self regulated learning. This study was mixed methods research with subject of this research was students of VII grade at SMPN 10 Semarang consist of three students from each self regulated learning (SR). Data in this research was the mathematical reasoning ability based on self regulated learning obtained from questionnaires, tests, observations, and interviews. The results of this study indicate that the quality of learning is good. (1) High SR subjects have mastered six reasoning indicators, (2) medium SR subjects are already mastering five reasoning indicators, and (3) low SR subjects are only able to master one reasoning indicator.